Extração dos parâmetros de módulos fotovoltaicos a partir da solução de um sistema de equações não lineares utilizando técnicas da região de confiança - Rodrigues, Pollyanna (2012)
This work presents a methodology for extracting characteristic parameters of a photovoltaic panel. From this methodology it is possible to verify the change of the parameters of a panel over time. After the presentation of the theory which is based the methodology used and the description of computer programs, an application is presented also allowing the analysis of the behavior of photovoltaic systems in shaded conditions set by the user. The application uses this methodology for the estimation of curves for each level of irradiation. The tool provides flexibility since allows the analysis of many different systems and configurations of shading. The user sets the level of shading and how many panels will be subject to that degree of brightness, thus enabling the analysis of series, shunts or mixed shading groups.